Weather-resistant and aging-resistant polyethylene pipe and preparation method thereof

By using synergistic effects of various materials such as high-density polyethylene resin, a weather-resistant and anti-aging polyethylene pipeline was prepared, which solved the problem of aging of polyethylene pipelines in sunlight and high and low temperature environments, and significantly improved the weather resistance of the pipeline. and anti-aging properties.

CN119081271BActive Publication Date: 2025-02-21TIANJIN MANHUA PIPE MATERIAL IND CO LTD

Patent Information

Application Number
CN202411578053.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-21
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

Polyethylene pipelines are easily affected by ultraviolet rays, oxygen and temperature changes when exposed to sunlight for a long time or in large environments with high and low temperature changes, resulting in a decrease in strength and toughness, and are prone to cracks and cracks, affecting their normal use.

Method used

Use high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin micropowder, nanosilicon dioxide, nanohexagonal boron nitride, polybenzimidazole fiber, sage acid, zinc glycyrrhizine, antioxidant 1010. Raw materials such as hindered amine light stabilizer, polydimethylsiloxane titanate cross-linked polymer and 3-methacryloyloxypropyltriethoxysilane are enhanced by special modification preparation method to enhance the pipeline Weather resistance and anti-aging properties.

Benefits of technology

It significantly improves the weather resistance and aging resistance of polyethylene pipes, extends its service life, and reduces aging and rupture problems caused by UV rays, oxygen and temperature changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to a weather-resistant and anti-aging polyethylene pipeline and a preparation method thereof, and belongs to the technical field of polymer materials. The pipeline adopts high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin powder, nano silicon dioxide, nano hexagonal boron nitride, polybenzimidazole fiber, carnosic acid, zinc glycyrrhetinate, antioxidant 1010, hindered amine light stabilizer, polydimethylsiloxane titanate cross-linked polymer, 3-methacryloxypropyl triethoxysilane as raw materials; wherein, polyimide resin powder, carnosic acid and zinc glycyrrhetinate are uniformly mixed, and then modified at 300°C to 350°C for 30min to 60min to obtain a modified product, which can better improve the weather resistance and aging resistance of the pipeline. Each component is compatible with each other, and a special modified preparation method is adopted to better play the synergistic effect of the components, and greatly improve the weather resistance and aging resistance of the polyethylene pipeline.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a weather-resistant and aging-resistant polyethylene pipe and a preparation method thereof. Background Art

[0002] Polyethylene is a polymer material made of ethylene monomers and can be used to prepare pipes. Polyethylene pipes are widely used in urban water supply and drainage, gas transportation, agricultural irrigation, chemical fluid transportation and other fields due to their good chemical stability, corrosion resistance, low friction coefficient, good flexibility and easy processing. In the field of water supply and drainage, polyethylene pipes can withstand a certain water pressure and will not rust and corrode as easily as metal pipes, thus ensuring the quality and safety of water supply. In terms of gas transportation, polyethylene pipes have good sealing and corrosion resistance, which can effectively prevent gas leakage and protect the lives and property of residents. In the field of agricultural irrigation, the flexibility of polyethylene pipes enables it to adapt to the laying requirements of different terrains, and its corrosion resistance can also ensure long-term use.

[0003] However, when polyethylene pipes are exposed to sunlight for a long time, they will be exposed to ultraviolet radiation. Ultraviolet rays can break the polyethylene molecular chains, resulting in a decrease in the strength and toughness of the pipes. In particular, polyethylene pipes used outdoors, such as pipes for irrigation and gas pipes laid in the open air, are more susceptible to ultraviolet rays. Long-term ultraviolet radiation can make the surface of the pipe brittle, crack, and even cause the pipe to rupture, affecting its normal use. Changes in temperature can also affect the weather resistance of polyethylene pipes. In high temperature environments, the strength of polyethylene pipes will decrease, while in low temperature environments, the pipes will become brittle and hard and easy to rupture. For example, in the hot summer, the temperature of polyethylene pipes exposed to the sun will rise to a high level, thus affecting their performance. In the cold winter, especially in the northern region, polyethylene pipes will become fragile and easily damaged due to the low temperature if proper insulation measures are not taken.

[0004] Polyethylene pipes will oxidize with oxygen in the air, and over time, oxidation will gradually reduce the performance of the pipe. Oxidation will cause the color of the pipe to darken, the surface to become rough, and will reduce the strength and toughness of the pipe. Especially in some environments containing corrosive gases or liquids, oxidation will be more obvious.

[0005] During use, polyethylene pipes are subject to various stresses, such as internal pressure, external pressure, bending stress, etc. These stresses will accelerate the aging process of the pipe. Long-term stress will orient the polyethylene molecular chains, resulting in uneven performance of the pipe. When the stress exceeds a certain limit, the pipe may rupture or leak.

[0006] In summary, although polyethylene pipes have many advantages, they still have some shortcomings in terms of weather resistance and anti-aging. In order to improve the performance and service life of polyethylene pipes, anti-ultraviolet agents, antioxidants, etc. are usually added; however, when exposed to sunlight for a long time, or in an environment with large changes in high and low temperatures, there are still deficiencies in quality and stability, which can easily lead to fluid leakage. Summary of the invention

[0007] The existing polyethylene pipes still have deficiencies in weather resistance and anti-aging. When anti-ultraviolet agents and antioxidants are added, there are still deficiencies in quality and stability when exposed to sunlight for a long time, or in an environment with large changes in high and low temperatures, which easily leads to fluid leakage problems. The present invention provides a weather-resistant and anti-aging polyethylene pipe and a preparation method thereof. The pipe uses high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin powder, nano-silicon dioxide, nano-hexagonal boron nitride, polybenzimidazole fiber, carnosic acid, zinc glycyrrhetinate, antioxidant 1010, hindered amine light stabilizer, polydimethylsiloxane titanate cross-linked polymer, and 3-methacryloxypropyl triethoxysilane as raw materials. The components are compatible with each other, and a special modified preparation method is adopted to better play the synergistic effect of the components, thereby greatly improving the weather resistance and aging resistance of the polyethylene pipe. The specific technical scheme is as follows:

[0008] A weather-resistant and aging-resistant polyethylene pipe, comprising the following raw materials in parts by mass: 40 to 50 parts of high-density polyethylene resin, 20 to 30 parts of linear low-density polyethylene resin, 5 to 10 parts of polyimide resin powder, 5 to 10 parts of nano-silicon dioxide, 2 to 5 parts of nano-hexagonal boron nitride, 0.5 to 1 part of polybenzimidazole fiber, 0.5 to 1.5 parts of carnosic acid, 0.1 to 0.5 parts of zinc glycyrrhetinate, 0.1 to 0.5 parts of antioxidant 1010, 2 to 4 parts of hindered amine light stabilizer, 1 to 3 parts of polydimethylsiloxane titanate cross-linked polymer, and 0.5 to 2 parts of 3-methacryloxypropyl triethoxysilane.

[0009] In the above technical solution, the particle size range of the polyimide resin powder is below 250 meshes, and the polyimide resin powder is a thermoplastic resin.

[0010] In the above technical solution, the particle size range of the nano silicon dioxide is below 200 nm; the particle size range of the nano hexagonal boron nitride is below 200 nm.

[0011] In the above technical solution, the diameter of the polybenzimidazole fiber is less than 50 μm, and the length is 0.5 mm to 2 mm.

[0012] In the above technical solution, the particle size range of the carnosic acid and zinc glycyrrhetinate is below 250 meshes.

[0013] The above-mentioned method for preparing a weather-resistant and aging-resistant polyethylene pipe comprises the following steps:

[0014] S1: Prepare raw materials according to mass proportion;

[0015] S2: drying high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin powder, nano-silicon dioxide, nano-hexagonal boron nitride, carnosic acid, and zinc glycyrrhetinate at 60° C. to 80° C. for 4 h to 6 h, respectively;

[0016] S3: uniformly mixing the nano-silicon dioxide and the nano-hexagonal boron nitride by air flow to obtain a mixture A;

[0017] S4: the polyimide resin powder, carnosic acid and zinc glycyrrhizinate are uniformly mixed, and then modified at 300°C to 350°C for 30min to 60min, and after cooling, crushed, passed through a 200-mesh sieve, and the sieve-under-sieve is taken to obtain a modified product B;

[0018] S5: Add high-density polyethylene resin, linear low-density polyethylene resin, polybenzimidazole fiber, polydimethylsiloxane titanate cross-linked polymer, and 3-methacryloxypropyl triethoxysilane into an internal mixer, and perform internal mixing at 140°C to 160°C for 5min to 10min. Then, add mixture A, antioxidant 1010, and hindered amine light stabilizer, and continue to perform internal mixing at 140°C to 160°C for 5min to 10min. Finally, add modifier B, and perform internal mixing at 160°C to 180°C for 5min to 10min to obtain an internal mixing material. The internal mixing material is passed through an extruder, extruded, and air-cooled to obtain a shaped pipe.

[0019] In S5 of the above preparation method, the rotating speed of the banburying is 100 r / min to 120 r / min.

[0020] In S5 of the above preparation method, the extruder is a single-screw extruder or a twin-screw extruder.

[0021] In S5 of the above preparation method, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 150°C to 170°C, the temperature of the compression zone is 170°C to 190°C, the temperature of the metering zone is 190°C to 210°C, and the temperature of the head zone is 210°C to 220°C.

[0022] In S5 of the above preparation method, the screw speed of the extruder is 30 r / min to 50 r / min, and the extrusion pressure is 10 MPa to 15 MPa.

[0023] The weather-resistant and aging-resistant polyethylene pipe and the preparation method thereof provided by the present invention have the following beneficial effects compared with the prior art:

[0024] 1. The pipeline of the present invention uses high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin powder, nano silicon dioxide, nano hexagonal boron nitride, polybenzimidazole fiber, carnosic acid, zinc glycyrrhetinate, antioxidant 1010, hindered amine light stabilizer, polydimethylsiloxane titanate cross-linked polymer, and 3-methacryloxypropyl triethoxysilane as raw materials. The components are compatible with each other and a special modified preparation method is adopted to better play the synergistic effect of the components, greatly improving the weather resistance and aging resistance of the polyethylene pipeline.

[0025] Second, the present invention adopts high-density polyethylene resin and linear low-density polyethylene resin compound. High-density polyethylene has high hardness and mechanical strength, which can provide basic structural support for the pipeline; linear low-density polyethylene resin has good toughness and environmental stress cracking resistance. Blending with high-density polyethylene resin can improve the overall toughness of the pipeline and reduce the possibility of cracks. However, polyethylene is susceptible to aging under the influence of ultraviolet rays, oxygen, temperature changes and other factors in the natural environment. Therefore, various auxiliary materials are designed to improve weather resistance and aging resistance. Polyimide resin has extremely high heat resistance, chemical corrosion resistance and mechanical strength, which can improve the high temperature resistance of the pipeline and reduce aging caused by high temperature. Nano-silicon dioxide can improve the hardness and wear resistance of the material, has a certain ultraviolet barrier effect, reduces the damage of ultraviolet rays to the pipeline, enhances the density of the material, and reduces the penetration of oxygen and moisture. Nano-hexagonal boron nitride improves the thermal stability of the material, reduces aging caused by temperature changes, has certain barrier properties, can prevent oxygen and moisture in the external environment from entering the interior of the pipeline, and slows down the aging process. The mechanical strength of polybenzimidazole fiber reinforced materials can reduce material damage and aging caused by external forces. It has high heat resistance and chemical stability, and can improve the aging resistance of pipelines in harsh environments. Carnosic acid can effectively inhibit the generation of free radicals and slow down the oxidative aging process of polyethylene. Zinc glycyrrhetinate has certain antibacterial and anti-ultraviolet properties, reducing microbial erosion and ultraviolet damage to pipelines, thereby improving weather resistance and aging resistance. Antioxidant 1010 is a synthetic antioxidant that can prevent the occurrence of oxidation reactions and extend the service life of pipelines. Hindered amine light stabilizers are stabilizers specifically for ultraviolet rays, which can absorb or quench free radicals generated by ultraviolet excitation to prevent ultraviolet damage to pipelines.

[0026] 3. Polydimethylsiloxane titanate cross-linked polymer can improve the flexibility and elasticity of the material and reduce cracks and aging caused by stress concentration. The polydimethylsiloxane part has good weather resistance and waterproofness, and can protect the pipeline from erosion by the external environment. 3-Methacryloxypropyl triethoxysilane is a coupling agent, which enhances the bonding force between the components and improves the overall performance and stability of the material.

[0027] 4. Polyimide resin powder, carnosic acid and zinc glycyrrhetinate have synergistic effects. Antioxidant synergy: Carnosic acid, as a natural antioxidant, works together with zinc glycyrrhetinate to more effectively inhibit the generation of free radicals and oxidation reactions. Polyimide resin powder further enhances the antioxidant effect by improving the overall stability of the material, and jointly delays the aging of polyethylene. Anti-ultraviolet synergy: The anti-ultraviolet performance of zinc glycyrrhetinate combined with the high temperature resistance and UV resistance of polyimide resin powder can better protect the pipeline from UV damage; carnosic acid also enhances the anti-ultraviolet effect to a certain extent. Antibacterial synergy: The antibacterial properties of zinc glycyrrhetinate and the chemical stability of polyimide resin powder work together to reduce the erosion of microorganisms on the pipeline and extend the service life of the pipeline. The combination of polyimide resin powder, carnosic acid and zinc glycyrrhetinate can greatly improve the weather resistance and aging resistance of polyethylene pipelines.

[0028] 5. The combined use of polyimide resin powder, carnosic acid, zinc glycyrrhetinate and polydimethylsiloxane titanate cross-linked polymer has a synergistic effect. Comprehensive improvement of weather resistance: The weather resistance and waterproofness of polydimethylsiloxane titanate cross-linked polymer are combined with the high temperature resistance and chemical corrosion resistance of polyimide resin powder and the antioxidant, UV resistance and antibacterial properties of carnosic acid and zinc glycyrrhetinate to comprehensively improve the weather resistance and aging resistance of pipelines. Protection synergy: Polydimethylsiloxane titanate cross-linked polymer forms a protective film on the surface of the pipeline to block the intrusion of external environmental factors, while polyimide resin powder, carnosic acid and zinc glycyrrhetinate enhance the stability and antioxidant capacity of the material from the inside, together providing stronger protection for the pipeline. Complementary performance: Each component plays its advantages in different aspects and complements each other. For example, polyimide resin powder provides mechanical strength and high temperature resistance, polydimethylsiloxane titanate cross-linked polymer improves flexibility and waterproofness, carnosic acid and zinc glycyrrhizinate provide antioxidant and antibacterial properties, which together improve the overall performance of the pipeline.

[0029] 6. The method of the present invention is designed to mix polyimide resin powder, carnosic acid and zinc glycyrrhetinate evenly, and then modify them at 300°C to 350°C to make the polyimide resin powder, carnosic acid and zinc glycyrrhetinate better in combination and synergistic effect, which can further improve the weather resistance and aging resistance of the polyethylene pipe.

[0030] 7. The method of the present invention dries the high-density polyethylene resin and the linear low-density polyethylene resin at 60° C. to 80° C. for 4 h to 6 h to remove moisture from the raw materials, prevent problems such as bubbles or hydrolysis from being generated during the processing, and improve the quality of the polyethylene pipe.

[0031] 8. The method of the present invention is to dry nano silicon dioxide, nano hexagonal boron nitride, carnosic acid, and zinc glycyrrhetinate at 60°C to 80°C for 4h to 6h respectively to remove the adsorbed water and volatile impurities on the surface thereof, thereby improving the dispersibility of each material. In particular, it can improve the mixing effect of carnosic acid, zinc glycyrrhetinate and polyimide resin micropowder, thereby improving the bonding uniformity, and more uniformly improving the weather resistance and aging resistance of polyethylene pipes. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.

[0033] Example 1

[0034] A weather-resistant and aging-resistant polyethylene pipe, comprising the following raw materials in parts by mass: 45 parts of high-density polyethylene resin, 25 parts of linear low-density polyethylene resin, 7.5 parts of polyimide resin powder, 7.5 parts of nano-silicon dioxide, 3.5 parts of nano-hexagonal boron nitride, 0.8 parts of polybenzimidazole fiber, 1 part of carnosic acid, 0.3 parts of zinc glycyrrhetinate, 0.3 parts of antioxidant 1010, 3 parts of hindered amine light stabilizer, 2 parts of polydimethylsiloxane titanate cross-linked polymer, and 1 part of 3-methacryloxypropyl triethoxysilane.

[0035] The above-mentioned method for preparing a weather-resistant and aging-resistant polyethylene pipe comprises the following steps:

[0036] S1: Prepare raw materials according to mass proportion;

[0037] S2: drying high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin powder, nano-silicon dioxide, nano-hexagonal boron nitride, carnosic acid, and zinc glycyrrhetinate at 70°C for 5 h respectively;

[0038] S3: uniformly mixing the nano-silicon dioxide and the nano-hexagonal boron nitride by air flow to obtain a mixture A;

[0039] S4: the polyimide resin powder, carnosic acid and glycyrrhetinic acid zinc are mixed uniformly, and then modified at 320°C for 50 minutes, and then pulverized after cooling, and passed through a 200-mesh sieve, and the sieve-under-sieve material is taken to obtain a modified material B;

[0040] S5: Add high-density polyethylene resin, linear low-density polyethylene resin, polybenzimidazole fiber, polydimethylsiloxane titanate cross-linked polymer, and 3-methacryloxypropyl triethoxysilane into an internal mixer, and perform internal mixing at 150° C. for 8 min at a speed of 100 r / min. Then, add mixture A, antioxidant 1010, and hindered amine light stabilizer, and continue to perform internal mixing at 150° C. for 6 min at a speed of 100 r / min. Finally, add modifier B, perform internal mixing at 170° C. for 8 min at a speed of 120 r / min, and obtain internal mixing material. The internal mixing material is extruded and molded by a twin-screw extruder, and air-cooled to obtain a shaped pipe.

[0041] Among them, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 160°C, the temperature of the compression zone is 180°C, the temperature of the metering zone is 200°C, and the temperature of the head zone is 215°C; the screw speed of the extruder is 40r / min, and the extrusion pressure is 12MPa.

[0042] Example 2

[0043] A weather-resistant and aging-resistant polyethylene pipe, comprising the following raw materials in parts by mass: 40 parts of high-density polyethylene resin, 20 parts of linear low-density polyethylene resin, 5 parts of polyimide resin powder, 5 parts of nano-silicon dioxide, 2 parts of nano-hexagonal boron nitride, 0.5 parts of polybenzimidazole fiber, 0.5 parts of carnosic acid, 0.1 parts of zinc glycyrrhetinate, 0.1 parts of antioxidant 1010, 2 parts of hindered amine light stabilizer, 1 part of polydimethylsiloxane titanate cross-linked polymer, and 0.5 parts of 3-methacryloxypropyl triethoxysilane.

[0044] The above-mentioned method for preparing a weather-resistant and aging-resistant polyethylene pipe comprises the following steps:

[0045] S1: Prepare raw materials according to mass proportion;

[0046] S2: drying high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin powder, nano-silicon dioxide, nano-hexagonal boron nitride, carnosic acid, and zinc glycyrrhetinate at 60°C for 4 h respectively;

[0047] S3: uniformly mixing the nano-silicon dioxide and the nano-hexagonal boron nitride by air flow to obtain a mixture A;

[0048] S4: the polyimide resin powder, carnosic acid and glycyrrhetinic acid zinc are mixed evenly, and then modified at 300° C. for 30 minutes, and then pulverized after cooling, and passed through a 200-mesh sieve, and the sieve-free product is taken to obtain a modified product B;

[0049] S5: Add high-density polyethylene resin, linear low-density polyethylene resin, polybenzimidazole fiber, polydimethylsiloxane titanate cross-linked polymer, and 3-methacryloxypropyl triethoxysilane into an internal mixer, and perform internal mixing at 140° C. for 5 min at a speed of 100 r / min. Then, add mixture A, antioxidant 1010, and hindered amine light stabilizer, and continue to perform internal mixing at 140° C. for 5 min at a speed of 100 r / min. Finally, add modifier B, perform internal mixing at 160° C. for 5 min at a speed of 100 r / min, and obtain internal mixing material. The internal mixing material is extruded and formed by a twin-screw extruder, and air-cooled to obtain a shaped pipe.

[0050] Among them, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 150°C, the temperature of the compression zone is 170°C, the temperature of the metering zone is 190°C, and the temperature of the head zone is 210°C; the screw speed of the extruder is 30r / min, and the extrusion pressure is 10MPa.

[0051] Example 3

[0052] A weather-resistant and aging-resistant polyethylene pipe, comprising the following raw materials in parts by mass: 42 parts of high-density polyethylene resin, 22 parts of linear low-density polyethylene resin, 6 parts of polyimide resin powder, 6 parts of nano-silicon dioxide, 2.5 parts of nano-hexagonal boron nitride, 0.6 parts of polybenzimidazole fiber, 0.8 parts of carnosic acid, 0.2 parts of zinc glycyrrhetinate, 0.2 parts of antioxidant 1010, 2.5 parts of hindered amine light stabilizer, 1.5 parts of polydimethylsiloxane titanate cross-linked polymer, and 0.8 parts of 3-methacryloxypropyl triethoxysilane.

[0053] The above-mentioned method for preparing a weather-resistant and aging-resistant polyethylene pipe comprises the following steps:

[0054] S1: Prepare raw materials according to mass proportion;

[0055] S2: drying high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin powder, nano-silicon dioxide, nano-hexagonal boron nitride, carnosic acid, and zinc glycyrrhetinate at 65°C for 4.5h respectively;

[0056] S3: uniformly mixing the nano-silicon dioxide and the nano-hexagonal boron nitride by air flow to obtain a mixture A;

[0057] S4: the polyimide resin powder, carnosic acid and glycyrrhetinic acid zinc are mixed uniformly, and then modified at 320°C for 40 minutes, cooled, crushed, and passed through a 200-mesh sieve, and the sieve-free product is taken to obtain a modified product B;

[0058] S5: Add high-density polyethylene resin, linear low-density polyethylene resin, polybenzimidazole fiber, polydimethylsiloxane titanate cross-linked polymer, and 3-methacryloxypropyl triethoxysilane into an internal mixer, and perform internal mixing at 145° C. for 6 min at a speed of 100 r / min. Then, add mixture A, antioxidant 1010, and hindered amine light stabilizer, and continue to perform internal mixing at 145° C. for 6 min at a speed of 100 r / min. Finally, add modifier B, perform internal mixing at 165° C. for 6 min at a speed of 100 r / min, and obtain internal mixing material. The internal mixing material is extruded and formed by a twin-screw extruder, and air-cooled to obtain a shaped pipe.

[0059] Among them, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 155°C, the temperature of the compression zone is 175°C, the temperature of the metering zone is 195°C, and the temperature of the head zone is 210°C; the screw speed of the extruder is 35r / min, and the extrusion pressure is 12MPa.

[0060] Example 4

[0061] A weather-resistant and aging-resistant polyethylene pipe, comprising the following raw materials in parts by mass: 50 parts of high-density polyethylene resin, 30 parts of linear low-density polyethylene resin, 10 parts of polyimide resin powder, 10 parts of nano-silicon dioxide, 5 parts of nano-hexagonal boron nitride, 1 part of polybenzimidazole fiber, 1.5 parts of carnosic acid, 0.5 parts of zinc glycyrrhetinate, 0.5 parts of antioxidant 1010, 4 parts of hindered amine light stabilizer, 3 parts of polydimethylsiloxane titanate cross-linked polymer, and 2 parts of 3-methacryloxypropyl triethoxysilane.

[0062] The above-mentioned method for preparing a weather-resistant and aging-resistant polyethylene pipe comprises the following steps:

[0063] S1: Prepare raw materials according to mass proportion;

[0064] S2: drying high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin powder, nano-silicon dioxide, nano-hexagonal boron nitride, carnosic acid, and zinc glycyrrhetinate at 80°C for 6h respectively;

[0065] S3: uniformly mixing the nano-silicon dioxide and the nano-hexagonal boron nitride by air flow to obtain a mixture A;

[0066] S4: the polyimide resin powder, carnosic acid and glycyrrhetinic acid zinc are mixed evenly, and then modified at 350°C for 60 minutes, cooled, crushed, and passed through a 200-mesh sieve, and the sieve-free material is taken to obtain a modified material B;

[0067] S5: Add high-density polyethylene resin, linear low-density polyethylene resin, polybenzimidazole fiber, polydimethylsiloxane titanate cross-linked polymer, and 3-methacryloxypropyl triethoxysilane into an internal mixer, and perform internal mixing at 160° C. for 10 min at a speed of 120 r / min. Then, add mixture A, antioxidant 1010, and hindered amine light stabilizer, and continue to perform internal mixing at 160° C. for 10 min at a speed of 120 r / min. Finally, add modifier B, perform internal mixing at 180° C. for 10 min at a speed of 120 r / min, and obtain internal mixing material. The internal mixing material is extruded and molded by a single screw extruder, and air-cooled to obtain a shaped pipe.

[0068] Among them, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 170°C, the temperature of the compression zone is 190°C, the temperature of the metering zone is 210°C, and the temperature of the head zone is 220°C; the screw speed of the extruder is 50r / min, and the extrusion pressure is 15MPa.

[0069] Example 5

[0070] A weather-resistant and aging-resistant polyethylene pipe, comprising the following raw materials in parts by mass: 48 parts of high-density polyethylene resin, 28 parts of linear low-density polyethylene resin, 8 parts of polyimide resin powder, 9 parts of nano silicon dioxide, 4 parts of nano hexagonal boron nitride, 0.8 parts of polybenzimidazole fiber, 1.3 parts of carnosic acid, 0.4 parts of zinc glycyrrhetinate, 0.4 parts of antioxidant 1010, 3.5 parts of hindered amine light stabilizer, 2.5 parts of polydimethylsiloxane titanate cross-linked polymer, and 1.5 parts of 3-methacryloxypropyl triethoxysilane.

[0071] The above-mentioned method for preparing a weather-resistant and aging-resistant polyethylene pipe comprises the following steps:

[0072] S1: Prepare raw materials according to mass proportion;

[0073] S2: drying high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin powder, nano-silicon dioxide, nano-hexagonal boron nitride, carnosic acid, and zinc glycyrrhetinate at 75°C for 5.5h respectively;

[0074] S3: uniformly mixing the nano-silicon dioxide and the nano-hexagonal boron nitride by air flow to obtain a mixture A;

[0075] S4: the polyimide resin powder, carnosic acid and glycyrrhetinic acid zinc are mixed uniformly, and then modified at 340°C for 55 minutes. After cooling, the mixture is crushed and passed through a 200-mesh sieve, and the sieve residue is taken to obtain a modified product B;

[0076] S5: Add high-density polyethylene resin, linear low-density polyethylene resin, polybenzimidazole fiber, polydimethylsiloxane titanate cross-linked polymer, and 3-methacryloxypropyl triethoxysilane into an internal mixer, and perform internal mixing at 155° C. for 8 min at a speed of 120 r / min. Then, add mixture A, antioxidant 1010, and hindered amine light stabilizer, and continue to perform internal mixing at 155° C. for 10 min at a speed of 120 r / min. Finally, add modifier B, perform internal mixing at 175° C. for 8 min at a speed of 120 r / min, and obtain internal mixing material. The internal mixing material is extruded and molded by a single screw extruder, and air-cooled to obtain a shaped pipe.

[0077] Among them, the extruder is divided into a feeding zone, a compression zone, a metering zone and a head zone: the temperature of the feeding zone is 165°C, the temperature of the compression zone is 185°C, the temperature of the metering zone is 205°C, and the temperature of the head zone is 220°C; the screw speed of the extruder is 45r / min, and the extrusion pressure is 14MPa.

[0078] In the above embodiments: the high-density polyethylene resin used is Sinopec's HDPE, TR210 high and low temperature resistant, high rigidity and UV-resistant extruded pipe grade polyethylene. The linear low-density polyethylene resin used is Maoming Petrochemical's LLDPE, DFDA-7042 film-grade extruded pipe grade low-density linear polyethylene, with a density of 0.92g / cm3. The particle size range of the polyimide resin micropowder used is below 250 mesh, and the polyimide resin micropowder is a thermoplastic resin, which comes from Huangshan Juxin New Materials Co., Ltd. The particle size range of the nano-silicon dioxide used is below 200nm. The particle size range of the nano-hexagonal boron nitride used is below 200nm, which comes from Anhui Kerun Nano Technology Co., Ltd. The diameter range of the polybenzimidazole fiber used is below 50μm, and the length range is 0.5mm~2mm, which comes from Shanghai Yichangsheng New Materials Co., Ltd. The particle size range of the carnosic acid used is below 250 mesh, and the carnosic acid content is 60%, which comes from Shaanxi Dennis Biotechnology Co., Ltd. The particle size range of the zinc glycyrrhetinate used is below 250 mesh, and it comes from the Shanghai Ke New Material Technology Co., Ltd. The hindered amine light stabilizer used is UV-770, which comes from Dongguan Kangjin New Material Technology Co., Ltd. The antioxidant 1010 used comes from Dongguan Xingyuan Chemical Co., Ltd. The polydimethylsiloxane titanate cross-linked polymer used comes from Liyang Ruipu New Materials Co., Ltd. The 3-(methacryloyloxy)propyl triethoxysilane used comes from Shandong Sodium Magnesium New Materials Co., Ltd.

[0079] Comparative Example 1

[0080] No nano hexagonal boron nitride is added to the polyethylene pipe, and the mass fraction of nano hexagonal boron nitride is replaced by high-density polyethylene resin; other parameters and methods are the same as in Example 1.

[0081] Comparative Example 2

[0082] No polybenzimidazole fiber is added to the polyethylene pipe, and the mass fraction of the polybenzimidazole fiber is replaced by high-density polyethylene resin; other parameters and methods are the same as in Example 1.

[0083] Comparative Example 3

[0084] No polydimethylsiloxane titanate cross-linked polymer is added to the polyethylene pipe, and the mass fraction of the polydimethylsiloxane titanate cross-linked polymer is replaced by high-density polyethylene resin; other parameters and methods are the same as in Example 1.

[0085] Comparative Example 4

[0086] No carnosic acid is added to the polyethylene pipe, and the mass fraction of carnosic acid is replaced by high-density polyethylene resin; other parameters and methods are the same as in Example 1.

[0087] Comparative Example 5

[0088] No zinc glycyrrhetinate is added to the polyethylene pipe, and the mass fraction of zinc glycyrrhetinate is replaced by high-density polyethylene resin; other parameters and methods are the same as in Example 1.

[0089] Comparative Example 6

[0090] No polyimide resin powder is added to the polyethylene pipe, and the mass fraction of the polyimide resin powder is replaced by high-density polyethylene resin; S4 is omitted in the preparation method, and the modifier B in S5 is replaced by carnosic acid and glycyrrhetinic acid zinc; other parameters and methods are the same as in Example 1.

[0091] Comparative Example 7

[0092] No polyimide resin powder, carnosic acid and zinc glycyrrhetinate are added to the polyethylene pipe, and the mass fractions of polyimide resin powder, carnosic acid and zinc glycyrrhetinate are replaced by high-density polyethylene resin; other parameters and methods are the same as in Example 1.

[0093] Comparative Example 8

[0094] No polyimide resin powder, carnosic acid, zinc glycyrrhetinate and polydimethylsiloxane titanate cross-linked polymer are added to the polyethylene pipe, and the mass fractions of each component are replaced by high-density polyethylene resin; other parameters and methods are the same as in Example 1.

[0095] Comparative Example 9

[0096] In the preparation method, S4 is omitted and the modified substance B is not prepared; in S5, the modified substance B is directly replaced by a mixture of polyimide resin powder, carnosic acid and zinc glycyrrhizinate; other parameters and methods are the same as in Example 1.

[0097] The materials of the above-mentioned embodiments and comparative examples were prepared into test samples and the following performance tests were carried out.

[0098] Polyethylene pipe sample: The sample specification is a pipe with an outer diameter of 32mm and a thickness of 3.5mm, with a clean surface and no obvious defects.

[0099] 1. Take some samples for testing (initial value): observe the appearance and find it is qualified; use an electronic universal testing machine to test the tensile strength and elongation at break; use a pressure testing machine to test the compressive deformation strength; use a hardness tester to measure the hardness of the pipe; the outer diameter is 32mm. The test results are shown in Table 1 below.

[0100] Table 1 Pipeline initial value performance test results

[0101]

[0102] It can be seen from the above results that the pipelines of Examples 1 to 5 have good mechanical properties. It can be seen from the results of Comparative Example 1 that not adding nano hexagonal boron nitride will reduce tensile strength, compressive strength and hardness. It can be seen from the results of Comparative Example 2 that not adding polybenzimidazole fiber will reduce tensile strength and compressive strength and improve elongation at break. It can be seen from the results of Comparative Example 3 that not adding polydimethylsiloxane titanate cross-linked polymer will make the component bonding poor, which will reduce tensile strength, compressive strength and hardness. It can be seen from the results of Comparative Example 4 that not adding carnosic acid has little effect on the initial mechanical properties of the pipeline. It can be seen from the results of Comparative Example 5 that not adding zinc glycyrrhetinate has little effect on the initial mechanical properties of the pipeline. It can be seen from the results of Comparative Example 6 that not adding polyimide resin powder will reduce tensile strength, compressive strength and hardness. It can be seen from the results of Comparative Example 7 that polyimide resin powder, carnosic acid and zinc glycyrrhetinate are not added to the polyethylene pipeline, and the mechanical properties of the pipeline are equivalent to those of the pipeline in Comparative Example 6. From the results of Comparative Example 8, it can be seen that without adding polyimide resin powder, carnosic acid, zinc glycyrrhetinate and polydimethylsiloxane titanate cross-linked polymer, the mechanical properties of the pipeline decrease relatively greatly. From the results of Comparative Example 9, it can be seen that without preparing modified substance B; modified substance B in S5 is directly replaced by a mixture of polyimide resin powder, carnosic acid and zinc glycyrrhetinate; the mechanical properties of the pipeline are comparable to those of Comparative Examples 6 and 7, and the influence is not significant.

[0103] 2. Weather resistance and anti-aging test:

[0104] 1. Take some samples and put them into the xenon lamp aging test box, light intensity: 0.55W / m² / nm (340nm); temperature: 60℃; humidity: 50%; spray water for 10 minutes every 2 hours.

[0105] 2. Carry out aging tests for different time periods: 30d, 60d.

[0106] 3. At each aging time point, take out some samples for the following tests (final value): Appearance inspection: observe whether there are cracks, discoloration, powdering and other phenomena on the surface of the pipeline; Mechanical property test: Use an electronic universal testing machine to test the tensile strength and elongation at break; Use a hardness tester to measure the hardness of the pipeline; Dimension measurement: Measure whether there is a significant change in the outer diameter.

[0107] 4. Analyze the test data results, record the time and degree of cracks, discoloration, powdering and other phenomena; calculate the change rate of tensile strength, elongation at break, hardness, and outer diameter; change rate = (final value - initial value) / initial value × 100%. The test results are shown in Table 2 below.

[0108] Table 2 Results of pipeline weather resistance and anti-aging test

[0109]

[0110] “-” means smaller.

[0111] Evaluation criteria for appearance:

[0112] Crack grade standard:

[0113] 1 point - Excellent: No cracks appear;

[0114] 2 points - Good: There are very fine cracks, the length of which is less than 1 / 10 of the circumference of the pipe, and the crack width is extremely narrow and almost invisible;

[0115] 3 points - Medium: The crack length is 1 / 10 to 1 / 5 of the pipe circumference, and the crack width is narrow, requiring careful observation to be found;

[0116] 4 points - poor: The crack length is 1 / 5 to 1 / 3 of the pipe circumference, the crack width is obvious and can be directly observed;

[0117] 5 points - Very poor: The crack length exceeds 1 / 3 of the pipeline circumference, the crack width is large, and has a significant impact on the structural integrity of the pipeline.

[0118] Color change grade standard:

[0119] 1 point - Excellent: The color is basically unchanged from before the aging test;

[0120] 2 points - Good: The color changes slightly, but not significantly, and is difficult to detect under normal lighting;

[0121] 3 points - Medium: The color change is more obvious, but still within the acceptable range and does not affect the overall appearance of the pipeline;

[0122] 4 points - poor: the color changes greatly, which is obviously different from that before the aging test and has a certain impact on the appearance of the pipeline;

[0123] 5 points - Very poor: The color changes seriously, which is completely different from that before the aging test, seriously affecting the appearance of the pipeline.

[0124] Powdering grade standard:

[0125] 1 point - Excellent: No powdering;

[0126] 2 points - good: very slight powdering, almost imperceptible by touch;

[0127] 3 points - medium: The degree of powdering is relatively light. You can feel a little powder when you touch it with your hand, but it does not affect the smoothness of the pipe surface.

[0128] 4 points - poor: The degree of powdering is obvious, there is a lot of powder when touched by hand, and the smoothness of the pipe surface is affected to a certain extent;

[0129] 5 points - Very poor: Severe powdering, a large amount of powder falls off when touched by hand, and the smoothness of the pipe surface is seriously damaged.

[0130] Appearance rating: The weighted average is calculated based on the grades of cracks, discoloration, and chalking. The weight of cracks is 40%, the weight of discoloration is 30%, and the weight of chalking is 30%. The overall score is calculated based on the grade scores of each aspect, and then the overall appearance grade is determined. Appearance rating = crack score × 40% + discoloration score × 30% + chalking score × 30%.

[0131] It can be seen from the above results that the pipes of Examples 1 to 5 have excellent weather resistance and aging resistance. It can be seen from the results of Comparative Example 1 that nano hexagonal boron nitride can improve the thermal stability of the material, reduce aging caused by temperature changes, and has certain barrier properties, blocking oxygen, moisture, etc. in the external environment from entering the interior of the pipe, slowing down the aging process; not adding nano hexagonal boron nitride will reduce the weather resistance and aging resistance of the pipe. It can be seen from the results of Comparative Example 2 that polybenzimidazole fiber has high heat resistance and chemical stability, and improves the aging resistance of the pipe in harsh environments; not adding polybenzimidazole fiber will reduce the weather resistance and aging resistance of the pipe. It can be seen from the results of Comparative Example 3 that polydimethylsiloxane titanate cross-linked polymer has good weather resistance and waterproof properties, protecting the pipe from erosion by the external environment; not adding polydimethylsiloxane titanate cross-linked polymer will reduce the weather resistance and aging resistance of the pipe. From the results of comparative example 4, it can be seen that carnosic acid, as a natural antioxidant, can effectively slow down the oxidative aging process of polyethylene; not adding carnosic acid will reduce the weather resistance and aging resistance of the pipeline. From the results of comparative example 5, it can be seen that zinc glycyrrhetinate has certain antibacterial and anti-ultraviolet properties, reduces the damage of ultraviolet rays to the pipeline, thereby improving the weather resistance and aging resistance; not adding zinc glycyrrhetinate will reduce the weather resistance and aging resistance of the pipeline. From the results of comparative example 6, it can be seen that polyimide resin powder has extremely high heat resistance, chemical corrosion resistance and mechanical strength, which can improve the temperature resistance and aging resistance of the pipeline; not adding polyimide resin powder will reduce the weather resistance and aging resistance of the pipeline. From the results of comparative example 7, it can be seen that the synergistic effect of polyimide resin powder, carnosic acid and zinc glycyrrhetinate greatly improves the temperature resistance and aging resistance of the pipeline. As a natural antioxidant, carnosic acid works together with zinc glycyrrhetinate to more effectively inhibit the generation of free radicals and oxidation reactions, and polyimide resin powder further enhances the antioxidant effect by improving the overall stability of the material, and jointly delays the aging of polyethylene. The anti-ultraviolet performance of zinc glycyrrhetinate is combined with the high temperature resistance and ultraviolet resistance of polyimide resin powder to better protect the pipeline from ultraviolet damage. From the results of comparative example 8, it can be seen that the weather resistance and waterproofness of polydimethylsiloxane titanate cross-linked polymer are combined with the high temperature resistance and chemical corrosion resistance of polyimide resin powder and the antioxidant, anti-ultraviolet and antibacterial properties of carnosic acid and zinc glycyrrhetinate, which comprehensively improves the weather resistance and aging resistance of the pipeline. The cross-linked polydimethylsiloxane titanate forms a protective film on the surface of the pipeline to block the intrusion of external environmental factors, while the polyimide resin powder, carnosic acid and zinc glycyrrhetinate enhance the stability and antioxidant capacity of the material from the inside, and jointly provide a more powerful protection for the pipeline.Each component plays its advantages in different aspects and complements each other. For example, polyimide resin powder provides mechanical strength and high temperature resistance, polydimethylsiloxane titanate cross-linked polymer improves flexibility and water resistance, carnosic acid and zinc glycyrrhetinate provide antioxidant and antibacterial properties, and jointly improve the comprehensive performance of the pipeline; greatly improve the heat resistance and anti-aging ability of the pipeline. From the results of comparative example 8, it can be seen that S4 is omitted and the modified substance B is not prepared; in S5, the modified substance B is directly replaced by a mixture of polyimide resin powder, carnosic acid and zinc glycyrrhetinate; it is proved that the synergistic effect of polyimide resin powder, carnosic acid and zinc glycyrrhetinate will be affected if no modification is performed.

Claims

1. A weather-resistant and aging-resistant polyethylene pipe, characterized in that: The polyethylene pipe includes the following raw materials in parts by weight: 40 to 50 parts of high-density polyethylene resin, 20 to 30 parts of linear low-density polyethylene resin, 5 to 10 parts of polyimide resin powder, 5 to 10 parts of nano-silicon dioxide, 2 to 5 parts of nano-hexagonal boron nitride, 0.5 to 1 part of polybenzimidazole fiber, 0.5 to 1.5 parts of carnosic acid, 0.1 to 0.5 parts of zinc glycyrrhetinate, 0.1 to 0.5 parts of antioxidant 1010, 2 to 4 parts of hindered amine light stabilizer, 1 to 3 parts of polydimethylsiloxane titanate cross-linked polymer, and 0.5 to 2 parts of 3-methacryloxypropyl triethoxysilane; The method for preparing the polyethylene pipe comprises the following steps: S1: Prepare raw materials according to mass proportion; S2: drying high-density polyethylene resin, linear low-density polyethylene resin, polyimide resin powder, nano-silicon dioxide, nano-hexagonal boron nitride, carnosic acid, and zinc glycyrrhetinate at 60° C. to 80° C. for 4 h to 6 h, respectively; S3: uniformly mixing the nano-silicon dioxide and the nano-hexagonal boron nitride by air flow to obtain a mixture A; S4: the polyimide resin powder, carnosic acid and zinc glycyrrhizinate are uniformly mixed, and then modified at 300°C to 350°C for 30min to 60min, and after cooling, crushed, passed through a 200-mesh sieve, and the sieve-under-sieve is taken to obtain a modified product B; S5: Add high-density polyethylene resin, linear low-density polyethylene resin, polybenzimidazole fiber, polydimethylsiloxane titanate cross-linked polymer, and 3-methacryloxypropyl triethoxysilane into an internal mixer, and perform internal mixing at 140°C to 160°C for 5min to 10min. Then, add mixture A, antioxidant 1010, and hindered amine light stabilizer, and continue to perform internal mixing at 140°C to 160°C for 5min to 10min. Finally, add modifier B, and perform internal mixing at 160°C to 180°C for 5min to 10min to obtain an internal mixing material. The internal mixing material is passed through an extruder, extruded, and air-cooled to obtain a shaped pipe.

2. The weather-resistant and aging-resistant polyethylene pipe according to claim 1, characterized in that: The particle size range of the polyimide resin powder is below 250 meshes, and the polyimide resin powder is a thermoplastic resin.

3. The weather-resistant and aging-resistant polyethylene pipe according to claim 1, characterized in that: The particle size range of the nano silicon dioxide is below 200nm; the particle size range of the nano hexagonal boron nitride is below 200nm.

4. The weather-resistant and aging-resistant polyethylene pipe according to claim 1, characterized in that: The polybenzimidazole fiber has a diameter range of less than 50 μm and a length range of 0.5 mm to 2 mm.

5. The weather-resistant and aging-resistant polyethylene pipe according to claim 1, characterized in that: The particle size range of the carnosic acid and zinc glycyrrhetinate is below 250 meshes.

6. The weather-resistant and aging-resistant polyethylene pipe according to claim 1, characterized in that: In S5, the rotating speed of the banburying is 100 r / min to 120 r / min.

7. The weather-resistant and aging-resistant polyethylene pipe according to claim 1, characterized in that: In S5, the extruder is a single-screw extruder or a twin-screw extruder.

8. The weather-resistant and aging-resistant polyethylene pipe according to claim 1, characterized in that: In S5, the extruder is divided into a feed zone, a compression zone, a metering zone and a head zone: the temperature of the feed zone is 150°C to 170°C, the temperature of the compression zone is 170°C to 190°C, the temperature of the metering zone is 190°C to 210°C, and the temperature of the head zone is 210°C to 220°C.

9. The weather-resistant and aging-resistant polyethylene pipe according to claim 1, characterized in that: In S5, the screw speed of the extruder is 30 r / min to 50 r / min, and the extrusion pressure is 10 MPa to 15 MPa.

Citation Information

Patent Citations

  • Low-density halogen-free flame retardant monocomponent titanate catalyzed room-temperature vulcanized silicone rubber and preparation method thereof

    CN103834172A

  • Titanate siloxane catalyst, and method for preparing Si-O-C type polyether silicone wax by using catalyst

    CN106916310A

Cited By

  • Preparation method of high-weather-resistant wear-resistant rubber material for floating conveying pipe

    CN120944339A

  • Method for producing high-weather-resistant wear-resistant rubber material for floating delivery pipe

    CN120944339B